A fully human scFv phage display library for rapid antibody fragment reformatting. Issue 10 (19th May 2015) - Li, Keyu; Zettlitz, Kirstin A.; Lipianskaya, Julia; Zhou, Yu; Marks, James D.; Mallick, Parag; Reiter, Robert E.; Wu, Anna M.
Abstract : Phage display libraries of human single-chain variable fragments (scFvs) are a reliable source of fully human antibodies for scientific and clinical applications. Frequently, scFvs form the basis of larger, bivalent formats to increase valency and avidity. A small and versatile bivalent antibody fragment is the diabody, a cross-paired scFv dimer (∼55 kDa). However, generation of diabodies from selected scFvs requires decreasing the length of the interdomain scFv linker, typically by overlap PCR. To simplify this process, we designed two scFv linkers with integrated restriction sites for easy linker length reduction (17-residue to 7-residue or 18-residue to 5-residue, respectively) and generated two fully human scFv phage display libraries. The larger library (9 × 10 9 functional members) was employed for selection against a model antigen, human N-cadherin, yielding novel scFv clones with low nanomolar monovalent affinities. ScFv clones from both libraries were reformatted into diabodies by restriction enzyme digestion and re-ligation. Size-exclusion chromatography analysis confirmed the proper dimerization of most of the diabodies. In conclusion, these specially designed scFv phage display libraries allow us to rapidly reformat the selected scFvs into diabodies, which can greatly accelerate early stage antibody development when bivalent fragments are needed for candidate screening.